TINJAUAN IMPLEMENTASI FRAGMENTASI ELASTIS PADA DATABASE NON-RELASIONAL UNTUK WEBSITE FORUM DISKUSI - , ARDIAN PRIMA ATMAJA, Dr.techn. Khabib Mustofa, S.Si, M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The existence of Web 2.0 increases the number of its user. This makes the web Provider implement a scalable system that can split the data into multiple server machines. At the same time, a relational database management system finds difficulty to create a elastic fragmentation system due to the demands of maintaining the data consistently. A website discussion forum that use an elastic fragmentation system consisting of two servers fragments (shard) to serve the growth of the number of documents stored is implemented in this research. The type of database used to construct the system is an open source non-relational documents oriented called MongoDB. The system will put partitions to the MongoDB database horizontally (sharding) and distributes them to nodes. In the final section, we will have comparative review about the number of concurrent users on the system availability and response time between a centralized system and two-shard fragmentation system. The result of this research, we find an increase in the number of concurrent users on intolerable availability and response time, on the two-shard fragmentation system rather than a centralized system. Increasing the number of concurrent users on the addition of a shard can reach up to 100% for document display units or tag and a new topic input, as well as up to 21.5% for document search unit. Response time is also increased to 12.5%.